Microcircuitry of the songbird basal ganglia nucleus area X - Budzillo, Agata (My University, 2015)
Understanding learning is one of the most basic human fascinations. As a nation we devote large amounts of resources to discovering therapeutic interventions for and preventing learning disabilities that arise developmentally (ex. mental retardation, autism, attention deficit hyperactivity disorder, dyslexia), due to insults to the nervous system (ex. stroke, traumatic brain injury), or with age (ex. Alzheimer’s and Parkinson’s diseases). Beyond repairing the brain, these efforts are progressively heading into the ethically gray territory of learning augmentation. Learning is a broad term that can encompass many different sensorimotor, cognitive, emotional and attentional processes on a wide spectrum of timescales. However, at their core all forms of learning occur through some form of interaction with the environment. One common strategy for learning that is used throughout the animal kingdom is trial-and-error. A central question guiding the present work is how the brain accomplishes the “trial” component of trial-and-error learning. In the following pages I will discuss theoretical frameworks that have shaped experimental studies of motor learning, proposed roles of the basal ganglia in regulating voluntary motor behavior and the advantages of neuroethological model systems, with a specific focus on songbirds. Finally, I will focus on the neural mechanisms thought to underlie the exploratory or “trial” component of vocal learning in the songbird, presenting evidence for a novel excitatory basal ganglia circuit component that may serve as one biophysical mechanism for the introduction of exploratory neural variability into motor behavior.
Thesis (Ph.D.)--University of Washington, 2015
Keywords: basal ganglia; motor learning; songbird; variability; Neurosciences; behavioral neuroscience